نصوص مسمارية غير منشورة من العصر البابلي القديم في المتحف العراقي - رضا, م.م حسين محمد (مجلة دراسات في التاريخ والآثار, 2020)
Abstract:The economic texts represent most of the cuneiform texts discovered in Mesopotamia. Its importance is providing great information about the economy of each city. In the Old Babylonian period (2000-1595 B.C), economic activity flourished, there were many texts related to sale and purchase contracts, loans and texts of the distribution of various materials to persons, This study deals with five unpublished cuneiform texts belong to the Iraqi Museum, the region of these texts are unknown except one belongs to Sippar (Tell Abu Habbah). All texts didn't have seals print, as well as four of them,  didn't contain a date formula, but it is possible to know its date based on the method of writing cuneiform signs which